Postproverbial irony in contemporary African cultural expressions (2024)
Irony is one of the most common literary techniques applied to the study of world literature, right from Classical times to the present day. Having reflected on proverbial irony as a literary concept, this research argues for the need to construe and critique the phenomenon of postproverbial irony, being featured in contemporary African cultural expressions but yet to be critically engaged. This paper, therefore, attempts to examine the theoretical perception of postproverbial irony as a literary phenomenon, particularly in some African languages such as Yoruba, Shona, Luganda, Kiswahili, and Luo, with applicable tenets of transgression and subversions as postproverbial theoretical model. The aim is to justify the literary presence of postproverbials as a complex but highly advanced cultural expression in postcolonial African societies. Against the backdrop of a lopsided view of only conditioning postproverbials as sheer blasphemous verbal/speech acts, part of the objectives of this paper is to showcase the irrefutable literary strength and depth of postproverbials as a viable literary concept as well as underscore its potential as part of critical research point in contemporary African cultural space.